The Classification of Leading Sectors Utilized Weighting Technique Analysis - Nurfariswan, Agi; Putra, Dwi Ardi Wicaksana (Universitas Negeri Semarang, 2022)
Related to the previous studies, there are still questions about what sectors are produced from several economic based approaches each year. This study aims to determine the “very potential” business fields to be developed. This research was led purposively in Sukamara Regency, Kalimantan Tengah Province thinking about that macroeconomic exhibition information actually should be additionally improved. Auxiliary information got by documentation at the Central Statistics Agency, specifically GRDP at 2010 Constant Market Prices for the 2015-2020 period. Arrangement of business fields is done utilizing a weighting come closer from the estimation of Location Quotient, Growth Ratio Model, Sectoral Contribution Percentage and Growth Rate, Shift Share Analysis, and Overlay. The consequences of the review show the pattern of the improvement of the quantity of driving areas that are getting less and less and not in any manner observe any area that is completely equipped for satisfying the normal financial based methodology presumptions consistently. Moreover, the weighting system carried out proposes a new contribution in determining the leading sectors with a clearer classification. Therefore, the results of this study at the same time provide recommendations for the need for an analysis of the leading sector every year as consideration for regional planning.